Identification and verification of YBX3 and its regulatory gene HEIH as an oncogenic system: A multidimensional analysis in colon cancer - Sun, Yiming; Li, Zhixi; Wang, Wensheng; Zhang, Xiuyang; Li, Wenjing; Du, Guangsheng; Yin, Jiuheng; Xiao, Weidong; Yang, Hua (Frontiers in Immunology, 2022)
The novel gene YBX3 is important for regulating translation and RNA catabolism and encodes a protein with a highly conserved cold-shock domain. However, its pathogenic roles across cancers (e.g., colon cancer) and its regulation remain unclear. We identified the pathogenic roles of YBX3 and its regulatory lncRNA HEIH in various cancers and investigated their effects on tumour progression in colon cancer. Methods including RNA pull-down, MS, TMA of 93 patients, qPCR of 12 patients with diverse clinicopathologic stages, and western blotting were performed. The pancancer analysis showed that YBX3 expression varies significantly among not only cancer types but also molecular and immune subtypes of the same cancer. Furthermore, its expression in colon cancer is clinically significant, and there is an obvious negative regulatory association between HEIH and YBX3. Among various cancers, especially colon cancer, YBX3 is more related than HEIH expression to the clinical features and prognosis of subgroups. ROC analysis showed that HEIH and YBX3 have similar predictive capacity in various cancers. DEG analysis in colon cancer revealed that they have similar hub gene networks, indicating an oncogenic system with strong overlap. The results also suggest that YBX3 is associated with tumour immune evasion via different mechanisms involving T-cell exclusion in different cancer types and by the tumour inﬁltration of immune cells. Interestingly, scRNA-seq revealed that HEIH inhibits this phenomenon. Our results also suggest that YBX3 expression is associated with immune or chemotherapeutic outcomes in various cancers, and YBX3 exhibited higher predictive power than 2 of 7 standardized biomarkers for response outcomes and overall survival of immune checkpoint blockade subcohorts. In colon cancer cell lines, lncRNA-HEIH and YBX3 associate. MS confirmed that YBX3 was pulled down with HEIH, and western blot showed that HEIH knockdown disinhibited YBX3. This study strongly suggests that lncRNA-HEIH/YBX3 is a pancancer immune-oncogenic system and could serve as a biomarker for diagnosis and prognosis and as a therapeutic target, especially in colon cancer.